Astroparticle, Particle and Space Physics, Detectors and Medical Physics Applications : Proceedings of the 9th Conference : Villa Olmo, Como, Italy, 17-21 October 2005 - Barone, Michele (Astroparticle, Particle, Space Physics, Radiation Interaction, Detectors and Medical Physics Applica., 2006)
The exploration of the subnuclear world is done through increasingly complex experiments covering a wide range of energies and in a large variety of environments - from particle accelerators, underground detectors to satellites and space laboratories. For these research programs to succeed, novel techniques, new materials and new instrumentation need to be used in detectors, often on a large scale. Hence, particle physics is at the forefront of technological advancement and leads to numerous applications. Among these, medical applications have a particular importance due to the health and soci.